Analisis Perbandingan Rasio Profitabilitas dan Economic Value Added (EVA) untuk Mengukur Kinerja Keuangan Perusahaan Sub Sektor Pariwisata Restoran dan Hotel yang Terdaftar di BEI Sebelum dan Selama Masa Pandemi Covid-19 - Sintani Zuyandita; Efni Cerya (Jurnal Ecogen, 2022)
The purpose of this study is too see if the Covid-19 pandemic has a significant impact on the company’s performance. This study was included in a quantitative study using comparative analysis an data processing using the SPSS 25 program. The data used are secondary data from Indonesia Stock Exchange (IDX) data released during the periode before the Covid-19 pandemic (2019) and during the Covid-19 (2020), tourism, restaurant, and hotel sub-sectors companies are seeing this happen. This study used a paired sample t-test, and the result of this study showed that net profit margin (NPM), return on equity (ROE), earnings per share (EPS), and economic value added (EVA) show that there is great significance. As for gross profit margin (GPM), it shows no significant difference in financial performance before and during the Covid-19 pandemic. Keywords: kinerja perusahaan, rasio profitabilitas, economic value added